Paradigma Pendidikan Kritis: Menuju Humanisasi Pendidikan - Sunhaji Sunhaji (Fakultas Tarbiyah dan Ilmu Keguruan IAIN Purwokerto, 2015)
The process of education must apply with â€œLearning Process Skillâ€, not â€œLearning Conceptâ€. Process approach marked with student centered curricula, not teacher centered. Role of teacher is as facilitator, mediator, dynamizing, organizing, and catalyst to apply â€œdialogâ€ as spirit of education process. Critical education model is an education that independent from internal-institutional fetter, social hegemony, or structured to maintain political and economical stability. These happen in the length of our national history, then produce tame-weak human accorded to system condition. Whereas, education is human right, even people right to enhance its maturity, self-identity, and independence to serve his function to his God. .